2019
DOI: 10.1051/e3sconf/201910000068
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of waste forest biomass: pelletization studies of torrefied sawmill wood chips

Abstract: The paper presents the effects pelletization process of torrefied waste forest biomass -sawmill wastes. The sawmill waste are generated in significant quantities and has significant energy potential. The use of torrefaction and pelletization process enables to produce mechanically durable fuel pellets. Aim of the studies was to evaluate the effect of different kind of additives (binders) to torrefied waste forest biomass on pelletization process characteristic (production capacity, energy consumption) and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The last method to improve the efficiency of this process, among those investigated by scientific research in the last five years, is the application of binders to biomass before torrefaction and pelletization. According to Rejdak et al [116], a very good performance was shown when modified wheat starch was used as a binder, which resulted in improvements in the mechanical characteristics of torrefied pellets. The same author found that a blend of natural wheat starch, molasses, and sodium lignosulfonate resulted in a pellet with good efficiency with slightly lower mechanical characteristics in comparison to one produced with modified wheat starch [116].…”
Section: Pre-and Post-treatmentsmentioning
confidence: 99%
“…The last method to improve the efficiency of this process, among those investigated by scientific research in the last five years, is the application of binders to biomass before torrefaction and pelletization. According to Rejdak et al [116], a very good performance was shown when modified wheat starch was used as a binder, which resulted in improvements in the mechanical characteristics of torrefied pellets. The same author found that a blend of natural wheat starch, molasses, and sodium lignosulfonate resulted in a pellet with good efficiency with slightly lower mechanical characteristics in comparison to one produced with modified wheat starch [116].…”
Section: Pre-and Post-treatmentsmentioning
confidence: 99%
“…All biomass, except for olive kernels, came from Poland. European countries including Poland have well-developed forestry, furniture and food processing industries, which generate significant amounts of organic waste [32][33][34]. Some of them are used for energy purposes by both professional and industrial power plants, wood pellet producers and individual recipients, e.g., in the form of pellets (domestic boilers).…”
Section: Coal Blend and Biocomponents Analysis And Preparation Of Bio...mentioning
confidence: 99%